اقتراح نظام متكامل لإدارة الوثائق عبر الإنترنت لفائدة المكتبت المركزيت بجامعت الوادي - غنابزية, حسان; حنانشة, سيف الاسلام (university of el oued/جامعة الوادي, 2020)
يعرف نظام الأرشفة و إدارة السجلات إلكترونيا في المكتبات الجامعية العديد من المشاكل والعوائق أهمها نقص توفير الخدمات و وصعوبة التواصل مع المنخرطين ,لذلك قمنا في هذه المذكرة باقتراح نظام آلي يخلصنا من عديد مشاكل الارشفة , يسهل التعامل مع المنخرطين , يوفر بحث متقدم , والاعتماد على مزامنة آلية للمحتوى الرقميThe electronic archiving and records management system in university libraries knows many problems and obstacles, the most important of which is the lack of service provision and the difficulty of communicating with those involved, so in this memorandum we proposed an automated system that saves us from many archiving problems, facilitates dealing with those involved, provides advanced search,and relies on synchronization A mechanism for digital content.
ليسانس إعلام ألي